LncRNA SPRY4‐IT1 regulates breast cancer cell stemness through competitively binding miR‐6882‐3p with TCF7L2. Issue 1 (17th November 2019) - Song, Xinyue; Zhang, Xiaoxue; Wang, Xinnan; Chen, Lianze; Jiang, Longyang; Zheng, Ang; Zhang, Ming; Zhao, Lin; Wei, Minjie
Abstract: SPRY4‐intronic transcript 1 has been found in several kinds of cancers, but the role of SPRY4‐IT1 in breast cancer stem cells has not been studied. We investigated whether SPRY4‐IT1 is involved in the promotion of breast cancer stem cells (BCSCs). We used qRT‐PCR to detect the expression of SPRY4‐IT1 in MCF‐7 cells and MCF‐7 cancer stem cells (MCF‐7 CSCs). The effects of SPRY4‐IT1 on the proliferation and renewal ability of breast cancer cells were investigated by in vitro and in vivo assays (ie in situ hybridization, colony formation assay, sphere formation assay, flow cytometry assay, western blotting, xenograft model and immunohistochemistry). The mechanism of SPPRY4‐IT1 as a ceRNA was studied by a dual‐luciferase reporter assay and bioinformatic analysis. In our study, SPRY4‐IT1 was up‐regulated in MCF‐7 CSCs compared with MCF‐7 cells, and high SPRY4‐IT1 expression was related to reduced breast cancer patient survival. Furthermore, SPRY4‐IT1 overexpression promoted breast cancer cell proliferation and stemness in vitro and in vivo. In addition, SPRY4‐IT1 knockdown suppressed BCSC renewal ability and stemness maintenance in vivo and in vitro. The dual‐luciferase reporter assays indicated that SPRY4‐IT1 as a sponge for miR‐6882‐3p repressed transcription factor 7‐like 2 (TCF7L2) expression. Taken together, these findings demonstrated that SPRY4‐IT1 promotes proliferation and stemness of breast cancer cells as well as renewal ability and stemness maintenance of BCSCs by increasing the expression of TCF7L2 through targeting miR‐6882‐3p.